2018
DOI: 10.3390/en11040865
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mild-Temperature Thermo-Alkaline Pretreatment on the Solubilization and Anaerobic Digestion of Spent Coffee Grounds

Abstract: Abstract:Mild-temperature thermo-alkaline pretreatment of spent coffee grounds (SCG) was studied to improve its solubilization and methanation. The simultaneous effects of NaOH concentration (0-0.2 M) and temperature (60-90 • C) were investigated. Significant solubilization of SCG was achieved by the pretreatment, particularly under high-NaOH-concentration and high-temperature conditions. However, adding NaOH above a certain concentration adversely affected the methane production. Therefore, the degree of solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 28 publications
(34 reference statements)
0
10
0
Order By: Relevance
“…To investigate methane yields of the solid remaining SCG extracted from organosolv treatment in the AD, the values of cumulative methane production were analyzed in BMP tests ( Figure 5). The result was estimated to be 36.0 mL-CH 4 /g-VS added , a relatively low value compared to conventional organic wastes used for methane production [13]. This result was inconsistent with a previous study, which reported that organosolv treatment could improve BMP of lignocellulosic substrate through degrading non-biodegradable lignocellulosic structures into easily digestible materials [40].…”
Section: Digestibility Of Scg Residues In a Batch Anaerobic Digestermentioning
confidence: 57%
See 2 more Smart Citations
“…To investigate methane yields of the solid remaining SCG extracted from organosolv treatment in the AD, the values of cumulative methane production were analyzed in BMP tests ( Figure 5). The result was estimated to be 36.0 mL-CH 4 /g-VS added , a relatively low value compared to conventional organic wastes used for methane production [13]. This result was inconsistent with a previous study, which reported that organosolv treatment could improve BMP of lignocellulosic substrate through degrading non-biodegradable lignocellulosic structures into easily digestible materials [40].…”
Section: Digestibility Of Scg Residues In a Batch Anaerobic Digestermentioning
confidence: 57%
“…Due to the organic richness of SCG, they have been subjects of anaerobic digestion (AD) in the quest to produce biogas using a sustainable biological approach [9]. SCG are especially rich in sugars, proteins and lipids, comprising 45.3% [10], 13.6% [11] and 9.3-16.2% [12], respectively, of its total weight, which makes SCG attractive subjects of AD research [13]. AD is one of the most favored biological processes that can retrieve energy from solid wastes under anaerobic conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In lignocellulosic biomass pretreatment process, alkaline concentration is a significant factor affecting degradation of the ester bonds between lignin-carbohydrate matrix [35]. Various study reported that the NaOH was suitable to remove lignin barrier, which increase the accessibility of enzyme to carbohydrate [37][38][39]. Carbohydrates of lignocellulosic biomass were comprised of cellulose and hemicellulose such as glucan, xyloglucan, xylan, arabinoxylan, mannan, gluco-or galactomannan [40].…”
Section: Effect Of Naoh Pretreatment On Carbohydrate Composition Of Sicyos Angulatusmentioning
confidence: 99%
“…Data on combined methods is rather limited. However, combined processes were reported to be fast methods (Kumar and Sharma, 2017;Kim et al, 2018).…”
Section: Rate Of Hydrolysismentioning
confidence: 99%